Differences in the vertical jumping power of football and volleyball players - Doder, D.; Dukic, B.; Kalentic, Z.; Sudarov, N.; Viduka, D. (3rd International Scientific Conference: Exercise and quality of life. April 12/13th 2013, 2013)
Explosive strength is equally important for the success in football and volleyball games. Explosive strength in jumping is estimated by vertical jump from crouch with modern diagnostic apparatus which allows an exact measurement of various parameters that are valued component of explosive strength. The aim of the research is to assess vertical jump explosive strength in the sample of 32 athletes (14 soccer players and 18 volleyball players), aged 14-17 years, and then applying multivariate statistical methods and univariate analyzes of variance (MANOVA / ANOVA) in variables of two foot jump without preparation (CJ), jump with both feet with the preparation (CMJ) and the maximum jump with preparation (CJ max) determine statistically significant differences between athletes in mentioned sports games. Multivariate statistical significance of differences between arithmetic means of football players (Mf) and volleyball players (Mo) obtained at the level of .00 (p= .00), and univariate procedures statistically significant differences exists only in relation to the maximal jump (CMJ), also at the level of .00 (p= .00). On the basis of obtained results it can be concluded that the statistically significant differences in the assessment of vertical jump explosive strength, exist primarily because of differences in morphological characteristics (body height and body weight) and situational movement structures (technical and tactical elements).